Age-related differences in time-based prospective memory: The role of time estimation in the clock monitoring strategy. Issue 6 (2nd July 2016) - Vanneste, Sandrine; Baudouin, Alexia; Bouazzaoui, Badiâa; Taconnat, Laurence
Abstract : Time-based prospective memory (TBPM) is required when it is necessary to remember to perform an action at a specific future point in time. This type of memory has been found to be particularly sensitive to ageing, probably because it requires a self-initiated response at a specific time. In this study, we sought to examine the involvement of temporal processes in the time monitoring strategy, which has been demonstrated to be a decisive factor in TBPM efficiency. We compared the performance of young and older adults in a TBPM task in which they had to press a response button every minute while categorising words. The design allowed participants to monitor time by checking a clock whenever they decided. Participants also completed a classic time-production task and several executive tasks assessing inhibition, updating and shifting processes. Our results confirm an age-related lack of accuracy in prospective memory performance, which seems to be related to a deficient strategic use of time monitoring. This could in turn be partially explained by age-related temporal deficits, as evidenced in the duration production task. These findings suggest that studies designed to investigate the age effect in TBPM tasks should consider the contribution of temporal mechanisms.